Compliance as Strategic Capability: Trust, Legitimacy, and Competitive Advantage in Digital Ecosystems - Dianti Eka Aprilia (UDEX Institute, 2025)
Regulatory intensification in digital ecosystems has repositioned compliance from episodic obligation to persistent organizational condition. Yet compliance remains predominantly framed as a cost of participation rather than a potential source of strategic differentiation. This article advances a capability-based perspective arguing that compliance becomes strategically consequential when embedded as an organizational capability rather than executed as minimal rule adherence. Integrating resource-based theory, dynamic capabilities, trust theory, signaling logic, and legitimacy scholarship, the analysis develops a mediated framework in which compliance capability generates competitive differentiation through relational and institutional mechanisms. Embedded and credible compliance routines function as costly signals of integrity and competence, fostering stakeholder trust under conditions of uncertainty. Stabilized trust accumulates into institutional legitimacy, which enhances ecosystem positioning through preferential partner selection, reduced coordination friction, and reputational resilience. Competitive advantage thus emerges indirectly through credibility-based amplification rather than direct regulatory conformity. The framework contributes a credibility-centered theory of strategic compliance and extends capability research into the governance domain of digitally mediated markets.